Inovasi Desain dan Simulasi Function Generator Dengan Integrasi Microcontroller - Adi Mulyadi; Muhammad Zainal Roisul Amin; Muchlis Abdi (Fakultas Teknik, Universitas Jember, 2023)
This paper discusses the innovation design and simulation of the function generator. The design uses the Atmega16 microcontroller and Integrated Circuit (IC) DAC0808, ATmega16, and LF351. The design and simulation were implemented at the Electrical Laboratory of the PGRI Banyuwangi University as a practical reference. The function generator test uses a frequency range of 30 Hz to 200 KHz with three waveforms of sine, pulse and ramp. The simulation results show that a sine wave is obtained at a frequency of 1 KHz and a period of 1120 us. Pulse waves are obtained at a frequency of 1 KHz and a period of 1150 us, while a ramp wave with a frequency of 1 KHz and a period of 1150 us. This proves that the function generator can generate signal waves at a frequency of 1 KHz with varying periods.